AGING WITH A PHYSICAL DISABILITY: FINDINGS AND IMPLICATIONS FROM THE CEREBRAL PALSY ADULT TRANSITION STUDY (CPAT). (11th November 2018) - Carollo, J J; Heyn, P C; Tagawa, A; Pan, Z
Abstract: We investigated cardiovascular disease risk factors (CVDRFs) and the association between CVDRFs and gross motor function with the Gross Motor Function Classification System (GMFCS) in 70 adults with cerebral palsy (CP) who were ambulatory. Metabolic syndrome (MetSyn) was identified in 17.1% of the cohort and it was higher than the 10% in age-matched individuals from the NHANES national data. We also used the Framingham Heart Study (FHS) CVD risk estimation and the FHS results support that this cohort is at greater risk for CVD as compared to the FHS population data. There was a positive correlation between gross motor function (GMFCS), waist circumference (p<0.05) and dyslipidemia (p<0.05). We also evaluated the associations between gait, CVDRFs, cognition, and grip strength. The CPAT study results supports that adults with CP are at higher risk for CVD and to premature aging, likely due to impaired mobility that leads to a sedentary lifestyle.